Drug-eluting implants - Salem, Aliasger K. (Henry Stewart Talks, 2022)
Types of drug eluting implants, Advantages and disadvantages of IDDS’s, GLIADEL Wafer, Implantable injectable gels, PLGA, Naltrexone, Microparticles